Antibiotics in mariculture organisms of different growth stages: Tissue-specific bioaccumulation and influencing factors. (1st November 2021) - Zhang, Xuanrui; Zhang, Jiachao; Han, Qianfan; Wang, Xiaoli; Wang, Shuguang; Yuan, Xianzheng; Zhang, Baiyu; Zhao, Shan
Abstract: Maricultured organisms are chronically exposed to water containing antibiotics but the bioaccumulative behavior of antibiotics in exposed organisms at different growth stages has received little attention. Here, we investigated the concentrations and tissue-specific bioaccumulation characteristics of 19 antibiotics during three growth stages (youth stage, growth stage, and adult stage) of various organisms ( Scophthalmus maximus, Penaeus vannamei, Penaeus japonicus, and Apostichopus japonicus ) cultivated in typical marine aquaculture regions, and explored the factors that could affect the bioaccumulation of antibiotics. Tetracyclines (TCs) and fluoroquinolones (FQs) were the dominant antibiotics in all organisms, and the total concentrations of the target antibiotics in fish ( S. maximus ) were significantly higher than those in shrimp ( P. vannamei and P. japonicus ) and sea cucumber ( A. japonicus ) ( p <  0.01). The bioaccumulation capacity of a class of statistically significant antibiotics in most samples was strongest during the youth stage and weakest during the adult stage. The antibiotics exhibited higher bioaccumulation capacity in lipid-rich tissues (fish liver and shrimp head) or respiratory organs (fish gill) than muscle. Our results also reveal significant metabolic transformation of enrofloxacin in fish. Different from previous studies, the logarithm bioaccumulation factor (log BAF) was positively correlated with log D lipw in low-biotransformation tissues (fish gill and muscle) rather than lipid-rich tissues (fish liver). Based on the calculated hazard quotients (HQ), doxycycline in fish muscle may pose a distinct risk to human health, which deserves special attention. Overall, these results provide insight into the bioaccumulation patterns of antibiotics during different growth stages and tissues of maricultured organisms. Graphical abstract: Image 1 Highlights: Fish exhibited the highest concentration of antibiotics in all studied species. The bioaccumulation capacity of antibiotics was the weakest in adult stage. The log BAF was positively correlated with the log D lipw in fish gill and muscle. Enrofloxacin had a significant metabolic transformation in fish. Doxycycline in fish may pose a distinct health risk to human.